From here to queer? Pitfalls and possibilities - Clarke,Victoria (2009)
In this article we consider the relationship between lesbian and gay psychology, latterly known as lesbian, gay, bisexual, trans and queer (LGBTQ) psychology and queer theory. We signal some ways that the field could become more intersectional by, for example, taking gender seriously, before turning our attention to queer theory. We explore some of the critiques of incorporating queer theory more fully into the field. In conclusion, we suggest that a tentative queering of LGBTQ psychology will provide fruitful possibilities for the future of the field.